Between Disputes and Discoveries - Rafaely Karolynne do Nascimento Campos (Revista Diálogo Educacional, 2025)
This study, an excerpt from a completed research project in the field of Early Childhood Education, aims to describe and analyze the relationships of conflict amongst young children during play. Initially, it is presented a discussion on childhood cultures, highlighting their connections to the studies of playing from a social and cultural perspective. Then, the methodological configurations of the research are detailed. The participants are 25 three-year-old children of both genders, enrolled in a municipal Early Childhood Education school. The data collection was based on the contributions of Childhood Sociology and conducted through an ethnographic approach. For this purpose, techniques such as participant observation, field diary records and video recordings were employed, enabling an in-depth analysis of the interactions and conflicts in play. The results indicate that, within the investigated group and context, situations of conflict and their forms of mediation are essential elements of childhood cultures. In these interactions, children learn to manage disputes and disagreements based on collectively constructed and shared rules, which contribute to the strengthening of interpersonal relationships and the organization of social groups. This process points to the development of fundamental social and interpersonal skills in the constitution of their identities.